«Сестра моя жизнь», экземпляр Маяковского - Kljatis, Anna (Wiener Slawistischer Almanach, 2024)
The article presents for the first time the original text of Boris Pasternak’s poem “Vy zaniaty nashim balansom…” (1921), which was written as an autograph on a copy of the book Sestra moia zhizn´, given to Vladimir Mayakovsky in the spring of 1922. Thanks to the discovery of Mayakovsky’s lost copy, the textological problems associated with this poem have been resolved, the lost (third) stanza has been restored, and the dating has been clarified. All this gives an opportunity to make corrections not only in the understanding of the text of the poem, but also in the historical details related to Pasternak’s position in 1921 and his relationship with Mayakovsky.